2019
DOI: 10.1111/pan.13636
|View full text |Cite
|
Sign up to set email alerts
|

Varying screen size for passive video distraction during induction of anesthesia in low‐risk children: A pilot randomized controlled trial

Abstract: Background: Preoperative anxiety affects up to 65% of children who undergo anesthesia induction and often results in uncooperative behavior. Electronic devices have been used to distract children to reduce anxiety and create a more enjoyable preoperative experience. Few studies have compared the effects of different video delivery systems on preoperative anxiety. Aims: The primary aim was to determine if a large projection-based video screen mounted to a patient's bed decreased anxiety when compared to a table… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 23 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…However, for some children, parent present inductions may paradoxically lead to increased anxiety [32]. Given that anesthesiologists have previously provided induction anxiolysis with distracting screen-based content, virtual reality offers a novel distracting anxiolytic with complete immersion [33–38]. A recent, well designed randomized controlled trial where virtual reality distraction was introduced immediately prior to mask induction of 5-to-12-year old children resulted in significantly lower anxiety [39 ▪▪ ].…”
Section: Periprocedural Care With Virtual Realitymentioning
confidence: 99%
“…However, for some children, parent present inductions may paradoxically lead to increased anxiety [32]. Given that anesthesiologists have previously provided induction anxiolysis with distracting screen-based content, virtual reality offers a novel distracting anxiolytic with complete immersion [33–38]. A recent, well designed randomized controlled trial where virtual reality distraction was introduced immediately prior to mask induction of 5-to-12-year old children resulted in significantly lower anxiety [39 ▪▪ ].…”
Section: Periprocedural Care With Virtual Realitymentioning
confidence: 99%
“…during a surgical course. Four of the five studies in this review demonstrated that TBID either reduced preoperative anxiety (2,4) or, at minimum, did not increase anxiety during the induction of anesthesia (1,5). Marechal et al found that the average m-YPAS scores (anxiety levels) over four measurements were decreased in the TAB group [14].…”
Section: Study #5 Distraction With a Hand-held Video Game Reduces Ped...mentioning
confidence: 82%
“…Traditionally, benzodiazepines, beta-blockers, and opioids have been used preoperatively to minimize preoperative anxiety. Although these medications reduce preoperative anxiety, several studies suggest that the emerging approach of tablet-based interactive distraction (TBID) offers a novel and promising alternative equally effective as a preoperative anxiolytic in pediatric patients [1][2][3][4][5][6][7]. TBID involves age-appropriate video games that have been preloaded onto a tablet (TAB) and given to a pediatric patient before administering anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…The interventions in these studies involved diverse technologies across the categories, that is, audio [ 33 , 49 ], light [ 42 ], sleep aids [ 19 ], communication support [ 21 ], others [ 46 ], and multiple components [ 24 , 51 , 52 ]. Of the 14 studies without significant effect on direct outcome measures, 8 studies, however, showed significant effects on delirium risk factors or symptoms, including pain [ 40 ], anxiety [ 35 , 36 , 38 , 50 ], agitation [ 54 ], hallucination [ 54 ], and factual memory encoding [ 45 ]. Six of the 8 studies using diverse technology-based interventions showed a significant effect on indirect outcome measures, including anxiety [ 39 ], agitation [ 43 ], sleep deprivation [ 44 ], or ICU readmission [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…First, most technology-based interventions addressed only one or a few delirium risk factors. For instance, interventions that used a dynamic light system [ 41 , 60 ] aimed to improve the patients’ sleep-wake cycle while interventions, including video distraction [ 34 , 35 , 43 ], aimed to reduce the anxiety of the patients. Such approaches are not in line with the frequently recommended multicomponent approach, which effectively targets the multifactorial origin of delirium [ 15 ].…”
Section: Discussionmentioning
confidence: 99%